Bionics and interior design - Bets, Svitlana (Theory and practice of design, 2022)
The use of bionics methods and structures to form a harmonious environment. The use of evolutionary experience of nature contributes to the emergence of innovative materials and technologies in various fields, including design. The research of bionics and bionics design of the last decade analyzed in the article can be divided into certain groups: study of architectural bionics, application of bionics in creating new materials — biomimetics, application of bionics for energy efficiency, and a small number of scientific papers on furniture bionics design and interior design. The scientific works mostly describe certain areas and methods of bionics or different types of their classifications. Therefore, in the course of the research the existing classifications of directions and methods of bionics research in the context of their implementation in design were generalized. The application of a systematic approach, the connection between basic research and the formation of bionics databases will help increase the efficiency of their further use in project activities. Characteristic features of bionics in interior design are described: stylized reproduction of natural forms and their structure; unity of interior elements; use of environmentally friendly innovative materials; application of the latest technologies: self-regulation, recovery and energy efficiency. Bionic principle of comparing the integrity and unity of the elements of a living organism should be used in design to form a harmonious environment. This applies both to the symbiotic relationship between architecture and the environment, and between architecture and interior elements. The use of bionics in interior design should be used not only to aestheticize the space, but also to achieve self-regulation, self-sufficiency, energy efficiency and environmental friendliness.